Pengantar Matlab Untuk Materi Konversi Suhu Pada Pembelajaran Fisika - Sri Endang Wahyuni; Puji Suharmanto (UNIVERSITAS INDRAPRASTA PGRI, 2022)
Matlab is one of the supporting media for learning motion physics in the Informatics engineering program at Indraprasta PGRI University. The purpose of using Matlab in learning physics as an application of physics material on computer-based learning media. The method of introducing Matlab in motion physics courses is the practice of making physics calculator applications using GUI (Graphical User Interface) and program code on temperature conversion material by students. Matlab software is easy to install on laptops and PCs so that hybrid learning-based motion physics meetings can be done anywhere. By making a physics calculator on temperature conversion material, it is hoped that informatics engineering students can be interested in studying physics both in theory and practice.